A Distinct Neurophenotype of Fearful Face Processing in Alcohol Use Disorder With and Without Comorbid Anxiety. (27th October 2020) - MacIlvane, Nicole; Fede, Samantha J.; Pearson, Emma E.; Diazgranados, Nancy; Momenan, Reza
Abstract : Background: Individuals with alcohol use disorder (AUD) can present with comorbid anxiety symptoms and often have deficits in emotional processing. Previous research suggests brain response is altered during facial affect recognition tasks, especially in limbic areas, due to either AUD or anxiety symptomology; however, the impact of both AUD and clinically significant anxiety symptoms during these tasks has not yet been examined. Methods: In this study, we investigated neural activation differences during an emotional face‐matching task. Participants ( N  = 232) underwent fMRI scanning, as part of a larger study. Three groups were investigated: individuals with diagnosed AUD and elevated anxiety traits (AUD + ANX, n  = 90), individuals with diagnosed AUD but non‐clinically significant levels of anxiety (AUD‐ANX, n  = 39), and healthy controls (HC, n  = 103). Results: Our results illustrate distinct neurophenotypes of AUD, where individuals with comorbid anxiety symptomology have blunted emotional face processing while those with singular AUD are hyperresponsive. Conclusions: This suggests AUD with anxiety symptomology may have a unique neurobiological underpinning, and treatment and intervention should be tailored to individual constellations of symptoms. Abstract : Individuals with AUD and with or without anxiety traits demonstrate differential patterns of neural engagement in emotion processing. Specifically, in AUD with accompanying anxiety, neural response to others' negative emotions is blunted; in AUD alone, it is hyperresponsive. This underlines the heterogeneity of AUD and the corresponding importance of personalized AUD treatment that considers comorbidities like anxiety. Moreover, it suggests differential vulnerabilities in the trajectory of AUD disease progression that could inform prevention or harm reduction approaches.